2015
DOI: 10.3184/174751915x14253193792383
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Odourant, 2-Mercapto-4-Heptanol

Abstract: 2-Mercapto-4-heptanol is a relatively new flavour compound that was recently approved as an ingredient by the Flavour and Extract Manufacturers' Association in 2013. Its synthesis, which we have accomplished in four-steps, involved firstly a Grignard reaction of n-butanal with allylmagnesium chloride to prepare 1-hepten-4-ol. This was epoxidised and then converted to 1,2-epithio-4-heptanol, reduction of which with LiAlH 4 gave the target compound in an overall yield of about 54%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…1-Hepten-4-ol 2, prepared by the Grignard reaction of allylmagnesium chloride with n-butanal, was epoxidised with MCPBA to produce 1,2-epoxy-4-heptanol 3, as previously described by us. 19 3 was then reacted with MsCl to give 1,2-epoxy-4-heptyl mesylate 4. The 1 H NMR spectra of epoxy alcohol 3 and its mesylate 4 showed that both of them were a mixture of diasteroisomers with a ratio of about 1/1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Hepten-4-ol 2, prepared by the Grignard reaction of allylmagnesium chloride with n-butanal, was epoxidised with MCPBA to produce 1,2-epoxy-4-heptanol 3, as previously described by us. 19 3 was then reacted with MsCl to give 1,2-epoxy-4-heptyl mesylate 4. The 1 H NMR spectra of epoxy alcohol 3 and its mesylate 4 showed that both of them were a mixture of diasteroisomers with a ratio of about 1/1.…”
Section: Resultsmentioning
confidence: 99%
“…1-Hepten-4-ol (2) and 1,2-epoxy-4-heptanol (3): Both prepared as previously described; the NMR data were consistent with those we have already reported. 19 1,2-Epoxy-4-heptyl mesylate (4): 1,2-Epoxy-4-heptanol 3 (2.6 g, 20 mmol) was dissolved in dry CH 2 Cl 2 (40 mL) and cooled to 0 °C. Triethylamine (5.6 mL, 40 mmol) and methanesulfonylchloride (2.3 mL, 30 mmol) were slowly added at 0-5 °C successively.…”
Section: Methodsmentioning
confidence: 99%